2010
DOI: 10.1097/iae.0b013e3181cfd3c6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Functional Changes Measured by Microperimetry in Neovascular Age-Related Macular Degeneration Treated With Ranibizumab

Abstract: Intravitreal injections of 0.5 mg ranibizumab determine progressive improvement of retinal sensitivity until 24 months, although visual acuity levels off after 6 months, suggesting that microperimetry may give additional information about macular function not given by visual acuity alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…11 In another trial, decrease in subretinal fluid volume and improvement in BCVA were strongly correlated, but no correlation was found between decreases in retinal and pigment epithelium detachment volumes and improvement in BCVA after three monthly ranibizumab injections. 19 Parravano et al 20 concluded that intravitreal injections of 0.5 mg ranibizumab were associated with progressive improvement of retinal sensitivity until 24 months, although BCVA values stabilized after 6 months, which suggested that microperimetry may give additional information about macular function that is missed by central VA testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…11 In another trial, decrease in subretinal fluid volume and improvement in BCVA were strongly correlated, but no correlation was found between decreases in retinal and pigment epithelium detachment volumes and improvement in BCVA after three monthly ranibizumab injections. 19 Parravano et al 20 concluded that intravitreal injections of 0.5 mg ranibizumab were associated with progressive improvement of retinal sensitivity until 24 months, although BCVA values stabilized after 6 months, which suggested that microperimetry may give additional information about macular function that is missed by central VA testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Bolz et al 18 conducted a prospective study to evaluate the functional and morphological effects of three loading doses of intravitreal ranibizumab in 29 patients (29 eyes) with previously untreated nvAMD. Although they observed an improvement in VA, central retinal thickness, and central retinal sensitivity after 1 month, they did not observe any additional benefit following the subsequent second and third injections.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis revealed that decrease in CMT was noted overall but VA increased only in the patients with classic type CNV. Gardner, Vujosevic and Parravano explained this finding by the duration of the macular disease (Gardner et al, 2002;Vujosevic et al, 2006;Parravano et al, 2010). They suggested that a prolonged intra-and/or subretinal edema could lead to persisting and irreversible damage to the photoreceptors that could influence the functional changes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared the observed change in best corrected VA with change in central retinal sensitivity pretreatment and one month after three consecutive treatments with ranibizumab in patients with neovascular AMD and they found that compared with microperimetry, VA seems to significantly underestimate the change in visual function experienced by patients treated with ranibizumab. Parravano et al (2010) found that intravitreal injections of 0.5 mg ranibizumab determine progressive improvement of retinal sensitivity until 24 months, suggesting that microperimetry may give additional information about macular function not given by visual acuity alone. In addition, changes of functional status, as expressed by mean retinal sensitivity and visual acuity, were not found to be related either to baseline status or to the observed CRT changes.…”
Section: Discussionmentioning
confidence: 99%